2015
DOI: 10.1364/oe.23.007550
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging master-slave OpenFlow controller arrangement to improve control plane resiliency in SD-EONs

Abstract: In this paper, we study how to improve the control plane resiliency of software-defined elastic optical networks (SD-EONs) and design a master-slave OpenFlow (OF) controller arrangement. Specifically, we introduce two OF controllers (OF-Cs), i.e., the master and slave OF-Cs, and make them work in a collaborative way to protect the SD-EON against controller failures. We develop a controller communication protocol (CCP) to facilitate the cooperation of the two OF-Cs. With the CCP, the master OF-C (M-OF-C) can sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Inspired by the aforementioned studies for packet SDN networks, we have designed and demonstrated a master-slave controller arrangement for SD-EONs in [31]. However, the problem of SCPE, i.e., the controller placement and related control channel planning for control service backup and migration, still has not been addressed and should be investigated carefully to make the solution more practical.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the aforementioned studies for packet SDN networks, we have designed and demonstrated a master-slave controller arrangement for SD-EONs in [31]. However, the problem of SCPE, i.e., the controller placement and related control channel planning for control service backup and migration, still has not been addressed and should be investigated carefully to make the solution more practical.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 4 shows the functional design of the OF-C for SCPE. The controller communication module (CCM) deals with the communication between OF-Cs using the controller communication protocol (CCP) developed in [19,31]. The purpose of the CCP is twofold.…”
Section: System Design For Live Control Service Backup and Migratimentioning
confidence: 99%
See 1 more Smart Citation
“…As well, the controller should maintain the health of the network over time. In implementing a centralized control system for the communication network to support smart infrastructure one needs to establish the reliability of such a system [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase scalability and avoid having a single point of failure, several controllers can be distributed throughout the network. Different architectures have been proposed: flat architectures (all controllers at the same level, e.g., primary/back-up solution [4,5]), or hierarchical architectures [6]. A key aspect in the design of reliable SDN networks is the controller placement problem, i.e., how many controllers to use and which location to deploy for each of them.…”
mentioning
confidence: 99%